Exogenous control over intracellular acidification: Enhancement via proton caged compounds coupled to gold nanoparticles and an alternative pathway with DMSO - CARBONE, MARILENA; ANTONAROLI, SIMONETTA; Sabbatella, G; Remita, H; Orlando, V.; Biagioni, M; Nucara, A. (Data in Brief, 2016)
Proton caged compounds exhibit a characteristic behavior when directly dosed into cells or being coupled to gold nanoparticles prior to the dosing.When irradiated in the near ultraviolet region, they release protons that interac twith intracellular HCO3- to yield H2CO3. The dissociation of carbonic acid,then, releases CO2 that can be distinctively singled out in infrared spectra. In the process of searching a pathway to augment the intra- cellular uptake of proton caged compounds,we probed the asso- ciation of 1-(2-nitrophenyl)-ethylhexadecylsulfonate (HDNS) with DMSO, an agent to enhance the membrane permeability.We found out a different UV-induced protonation mechanism that opens up to new conduits of employing of proton caged compounds.